Preferential CO Oxidation on a Highly Active Cu Single Atom Catalyst Supported by Ce−TiOx. Issue 23 (7th November 2022) - Abed, Hayder; Mosrati, Jawaher; Abdel‐Mageed, Ali M.; Cisneros, Sebastian; Huyen Vuong, Thanh; Rockstroh, Nils; Bartling, Stephan; Wohlrab, Sebastian; Brückner, Angelika; Rabeah, Jabor
Abstract: A heterogeneous single‐atom catalyst (SAC) based on a tiny Cu loading (0.05 wt.%) supported on CeO2 −TiO2 (Ce/Ti=0.18) shows very high Cu mass‐normalized CO oxidation activity, 100 % selectivity for CO2 between 60 and 100 °C and essentially no deactivation during 17 h on stream in the preferential oxidation of CO (PROX) at 120 °C. Based on state of the art, this catalyst is among the most active and PROX‐selective catalysts. Employing a combination of ex‐situ and operando methods, we infer that the isolated Cu single sites are incorporated with redox‐active Cu 2+ −O−Ce 4+ ⇆Cu + −□−Ce 3+ moieties connected by labile oxygen and are exposed on the surface of highly dispersed ceria. This high dispersion is promoted by TiO2 which itself does not participate in redox steps during PROX, as Ti ions remain essentially tetravalent while Cu and Ce undergo reversible redox shuttles. Abstract : Cu on CeO2 −TiO2 for CO oxidation : Isolated Cu single atom catalyst supported on CeO2 −TiO2 for high‐performance preferential oxidation of CO in H2 ‐rich stream has been develop and deeply investigated by multi‐operando techniques such as DRIFT, NAP‐XPS, and EPR. The results reveal that the origin of the high catalytic performance is attributed to the enhancement of the −Cu 2+ −O−Ce 4+ − and −Cu + −□−Ce 3+ − redox shuttle.